Human papillomavirus genotype detection in recurrent respiratory papillomatosis (RRP) in Colombia12. Issue 2 (24th February 2012) - Sanchez, Gloria I.; Jaramillo, Roberto; Cuello, Gustavo; Quintero, Katherine; Baena, Armando; O'Byrne, Adriana; Reyes, Antonio Jose; Santamaria, Consuelo; Cuello, Harold; Arrunategui, Anamaria; Cortez, Armando; Osorio, German; et al.
Abstract Background Knowledge on human papillomavirus (HPV) genotype distribution in recurrent respiratory papillomatosis (RRP) is essential to assess the impact of HPV vaccine. It is provided information for Colombia. Methods In all, 189 RRP primary cases diagnosed between 1985 and 2009 were identified from 5 pathology laboratories of Cali and Medellin, Colombia. HPV DNA testing in 129 cases that fulfilled inclusion criteria (available paraffin blocks, amplifiable DNA, and confirmed histologic diagnosis of RRP) was performed by the SPF‐10/LiPA25 assay (version 1). Results Of all cases 36.1% were juvenile (<12 years old) and a majority of adults were males (p = .09); 95% of cases were HPV positive. HPV 6, 11, and 16 contributed to 69%, 27.1%, and 7.8% of all HPV positive cases. Twelve cases (9.3%) showed multiple infections; 8 of these were HPV 6 or 11 positive. Conclusions HPV prophylactic vaccine including HPV 6 and 11 may have a major impact against RRP. © 2012 Wiley Periodicals, Inc. Head Neck, 2013